Effect of Shengmai San on Insulin Resistance, Tumor Necrosis Factor-Alpha and Oxidative Stress in Rats Fed on a High-Fat Diet - 姚賢宗(Hsien-Tsung Yao); 江孟燦(Meng-Tsan Chiang); 李宗貴(Chong-Kuei Lii); 張毅偉(Yi-Wei Chang); 謝夙惠(Su-Huei Hsieh); 林佳璇(Jia-Hsuan Lin); 鄒瑞煌(Ruey-Hwang Chou); 葉燈光(Teng-Kuang Yeh) (Yàowu shi͡p︡in fenxi, 2011)
Shengmai San (SMS) is a well-known traditional Chinese medicine formula prescribed for patients with coronary heart disease (CHD). Insulin resistance is the most likely explanation for the development and progression of this disease. To investigate the effect of SMS on high-fat diet-induced insulin resistance, inflammatory cytokine production and oxidative stress, male Wistar rats were fed with low-fat control diet, high-fat diet and high-fat diet supplemented with 4% SMS for eight weeks. An oral glucose tolerance test was conducted in the seventh week. Rats fed the SMS diet had significantly lower plasma fructosamine concentration (p＜0.05) and tended to have lower (p＜0.1) AUC values of plasma glucose and insulin concentrations after glucose challenge, compared to those fed the high-fat diet. Moreover, SMS reduced TNF-α and lipid peroxidation levels in the liver and heart. However, SMS had no effect on fasting plasma concentrations of glucose, insulin, triglyceride, non-esterified fatty acids, total cholesterol, HDL-cholesterol and insulin resistance index (homeostasis model assessment; HOMA) in rats. Our results show that SMS may have little or no significant effect on reducing insulin resistance, but display anti-oxidative and anti-inflammatory properties.